The status of energy access in three regions of Tanzania: Baseline report for an urban grid upgrading and rural extension project - Gunther Bensch; Merle Kreibaum; Tukae Mbegalo; Jörg Peters; Natascha Wagner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
More than 1.1 billion people in developing countries lack access to electricity with a large share living in rural Africa. It is hypothesized that economic and human development are difficult without electricity access. Tanzania is one of the poorest countries in the world and the country's huge geographical extent and low population density makes infrastructure development such as electrification a particularly difficult exercise. The electrification rate is extremely low at around 46 percent in urban and 4 percent in rural areas. The access to reliable modern energy has become one of 17 Sustainable Development Goals (UN 2014) and the international community has embarked on a historical mission through the United Nations initiative Sustainable Energy for All (SE4All) that strives to provide electricity to everybody by 2030. Investment requirements to achieve this goal are enormous and large gaps exist so far. Additional investment initiatives are required.
urn:nbn:de:101:1-201706141551
Keywords: 330